Nano zinc – titanium – cerium Coating on BIS 2062 Boat building Carbon steel for Corrosion Protection - Ashraf, P. Muhamed; Anuradha, R. (Fishery Technology, 2020)
The corrosion inhibition ability of three nano oxides, zinc oxide, titanium oxide and cerium oxide coating over BIS 2062 carbon steel was studied. Morphology of the coating evaluated using SEM and AFM techniques and it showed uniform coverage over the surface and lower roughness than untreated steel. Electrochemical measurement in 3.5% NaCl showed 3.5-fold increase in polarization resistance than bare steel. The electrochemical impedance spectroscopy data was exhibited comparable results as that of linear polarization studies. The nano xode mixture having 0.01% each of zinc and titanium and 0.02% cerium showed adequate corrosion protection under the marine environment.